Analisis Kinerja Ruas Jalan Denpasar Gilimanuk Segmen Kecamatan Mengwi - I Wayan Gede Darma Yoga (Universitas Pendidikan Nasional, 2023)
Badung Regency is one of the districts that has a very high intensity level of vehicle movement. This is because the Badung district in general in the province of Bali is the entry point for land transportation traffic from western Indonesia, in this case from the islands of Sumatra and Java to the province of Bali. Jalan Denpasar Gilimanuk is one of the busiest national roads in the province of Bali, this is because Jalan Denpasar Gilimanuk is a road that acts as a connecting artery between the islands of Sumatra, Java, Bali and Lombok. Most of all types of logistics transportation involving the province of Bali pass through this Denpasar Gilimanuk road. Given its dense intensity, the Denpasar Gilimanuk road often experiences traffic jams, especially in the Mengwi District segment, Badung Regency. The method used in calculating the performance of this road section is to use the calculation method from MKJI (1997). In calculating the performance analysis of road sections using the MKJI method, it is influenced by several factors, namely basic capacity, road width, road separation, side barriers and city size. From the results of the analysis it was found that the peak traffic hours on Jalan Denpasar Gilimanuk were at 11.30-12.30, the traffic volume obtained from the field survey was 2889.6 pcu/hour. The road capacity obtained from the results of the analysis is 3446 pcu/hour. By comparing the value of the volume with the capacity (V/C Ratio) the value of the degree of saturation (DS) is 0.83. From the results of the analysis, when plotted into the table, Minister of Transportation Regulation No. KM 14 of 2006, it can be concluded that the service level for the Denpasar Gilimanuk road during peak hours is at the service level